2019
DOI: 10.1371/journal.pone.0217811
|View full text |Cite
|
Sign up to set email alerts
|

Injecting-related trust, cooperation, intimacy, and power as key factors influencing risk perception among drug injecting partnerships

Abstract: Sharing of injection drug use paraphernalia is a dyadic process linked to the transmission of HIV and hepatitis C virus (HCV). Despite this, limited research exists identifying specific dyadic interpersonal factors driving injecting partners’ engagement in needle/syringe and ancillary injecting equipment sharing among young adults. Using semi-structured in-depth interview data collected between 2014 and 2015 from twenty-seven people who inject drugs (PWID), we applied an inductive approach to identify key inje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…Our study supports others showing that syringe sharing is common among mixed-gender dyads within the context of a close sexual relationship (e.g., condomless sex) [ 37 41 ], while equipment sharing was simply more likely in a sexual relationship. Similar to other studies on PWID, closeness and trust were important interpersonal factors [ 40 , 42 , 43 ]; PWID in our study were more likely to share syringes with those who they trusted and who provided personal support.…”
Section: Discussionsupporting
confidence: 87%
“…Our study supports others showing that syringe sharing is common among mixed-gender dyads within the context of a close sexual relationship (e.g., condomless sex) [ 37 41 ], while equipment sharing was simply more likely in a sexual relationship. Similar to other studies on PWID, closeness and trust were important interpersonal factors [ 40 , 42 , 43 ]; PWID in our study were more likely to share syringes with those who they trusted and who provided personal support.…”
Section: Discussionsupporting
confidence: 87%
“…All of these factors may also have contributed to the lack of association found between sexual partnerships and HCV infection outcomes, a result we found to be unusual given previous research shows that overlapping sexual/injecting partnerships have been shown to be associated with differential risk exposures for HCV infection [24, 31, 48]. The interpersonal dynamics influencing behaviors sexual relationships may be different within injecting partnerships [44]. We note that even when the partners are not sexual partners, there may be close and reciprocating social ties formed through the relational qualities of injecting together not captured by the term ‘sex partner’ that is likely to be associated with a heightened risk of unsafe injection practices.…”
Section: Discussionmentioning
confidence: 99%
“…Since HCV prevalence is higher in older injectors, these results suggest that behavioral factors, potentially seroadaptive behaviors, may be operational in reducing HCV incidence, as has been seen with HIV in MSM dyads [43]. Interpersonal dynamics that contribute toward how partners inject is associated with trust, intimacy and cooperation, which also contribute to perceived risk for infection [44]. These injecting related interpersonal dynamics may differ based on age differences in injecting partnerships.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, perception of risk at pretest was high for our program (3.55 of 4, where 4 represents “great risk”), so it is possible that a ceiling effect limited the ability to measure improvement. While not specific to our priority population, other literature has suggested that perceived HIV risk may be higher among individuals who are engaged in relationships where sex, drug use, and needle sharing co-occur than among individuals who engage in condomless sex alone (Koku & Felsher, 2020), and that interpersonal relationships and power dynamics play a meaningful role in how needles are used, and perceived risk thereof (Morris et al, 2019). Thus, it is not unreasonable that individuals’ perception of risk of using unsanitized needles would be high in a given sample, regardless of behavioral intentions related to needle sharing and reuse.…”
Section: Discussionmentioning
confidence: 99%